Strategies used by Midlands State University students to cope with academic stress - Machemedze, Tawanda D. (Midlands State University, 2014)
The researcher sought to study on the strategies used by Midlands State University students to cope with academic stress. The research was enriched with a couple of theories,relavant literature by other authors and previous studies that supported the research. The students were sampled using stratified random sampling. Stratification comprised of strata that are first, second and fourth year students from the Psychology Department in the Faculty of Social Sciences who made up a total of one fifty six students with equal representation of males and females. The research instrument used were questionnaires which constituted demographic data, copying strategies and academic stressors. Data was analyzed through SPSS using descriptive statistics and was presented in the form of charts and bargrahps and tables. Major findings were that social support coping strategies are the most used by university students whilst emotional and avoidance coping strategies are the least used. The study also revealed that the four most common sources of stress included registration procedures, financial burdens ,in adequate material to do assignments and workload whilst the least sources of academic stress were poor performances and poor performances. Apart from that, the study revealed that coping strategies differ by gender with females students using more of emotional coping strategies and social support strategies whilst male students use more of distancing coping strategies and avoidance coping strategies. Recommendations to the university such as creating new strategies and strengthening existing initiatives were made to the university towards curbing academic stress .